Obowiązek rezydencji prałatów i kanoników katedralnej kapituły chełmskiej w Krasnymstawie - Pałka, Paweł (Prawo Kanoniczne, 1985)
T h e q u e stio n show ed in a T itle of th is m o n o g rap h re g a rd th e C h a p te r c o n stitu te d in C hełm in v irtu e of F o u n d a tio n A ct of th e K in g W ład y sław Jag iełło fro m 1429, a n d tram sfered in 1490 to K ra sn y staw . F o r th e en d o v em e n t of thfe C h a p ter com posed in itia l fro m 2 p re la te s a n d 10 canons d em an d e d th e K ing, th a t a ll m em b ers of t-he C h ap te r sh o u ld resid e by th e C a th e d ra l to k eep a sp len d o r of G od’s C u lt a n d in o rd e r th a t th ey should say p re y e rs fo r th e fo u n d er, h is fam ily, th e deceased w ifes a n d fo r a p ro sp e rity of K ingdom . S im ila r resid en ce d em an d e d also T re n t’s C ouncil a n d C h a p te r’s C h a rte rs a p p ro v ed b y B ishop W ojciech Sobi-ejuski fro m S taro izrzeb iec in 1572. C ause a pooor endow m ent of th e C haiptar th e p ré la ts a n d th e canons alm o st since a b eg in n in g assu m ed o th e r P a s to ra l’s b enefices in a D iocese, it w as la ck of th e fu n d s a d e q u a te fo r all m em b ers of a C h a p ter (in itial 12, a n d la te r 19) fo r su b sisten ce b esid e th e C ath e d ra l, chiefly th a t in som e y e ars th e e states of C h a p te r w e re dev a sta te d b y T a ta r’s invasions. G oing th ro u g h th e y ro u n d of d u ties th e B ishops w e re w a tc h in g ab o u t th e fu lfilm e n t th e ir o b lig atio n of R esidence by p ré la ts an d canons, a n d th ey w a tc h in g also th a t G od’s cu lt sh o u ld be rig h tly p erfo rm ed , a t le a s t successively b y a p a rt of th e m em b ers of a C h ap te r. I t w as se ttle d a cu sto m co n cern in g th e p e rfo rm a n ce o f a C ult a n d th e fu lfilm e n t of d u ties re la te d to, in a fa rm of ro ta tio n design a te d by a C h ap ter. I t w e re w eek ly ro ta tio n , a n d o ften m o n th ly, com posed by tw o p ré la ts or canons. S om etim e o n ly th e y w e re re p la ce d b y h o n o ra ry canons. A lso th is m a n n e r of resid en ce w aist ev e ry tim e co n serv e v ery e x actly , w h a t w as show ed in th e reco rd s of C h a p te r’s sessions a n d in R e fo rm atio n al D ecrees issu ed b y B ishops a fte r th e acco m p lish m en ts of C a th e d ra l v isitatio n s. I t w as in a p rin c ip le d u rin g a ll tim e of th is C h a p te r ex istatio n , w h ich w as ab ro g a te d to g e th e r w ith th e ab ro g a tio n o f C helm ’s diocese by a P o p e P iu s V II w ith a B u lla Q u em a d m o d u m R o m a n o ru m P o n tific u m fro m O ct. 9, 1805, p u t in to effect in 18C7, sim u ltan eo u sly to a c rea tio n of L u b lin ’s diocese a n d it C a th e d ra l C h ap ter.